Numerical Investigation of Flow Patterns and Concentration Profiles in Y-Mixers - Babu, Harsha Vardhan; Sahu, Swati; Haderlein, Michael; Peukert, Wolfgang; Verma, Nishith (Journal of Chemical Engineering & Process Technology, 2016)
The fluid flow patterns and associated concentration fields in Y-mixers are investi- gated using lattice Boltzmann method-based models. The focus lies on the impact of the mixing angle on the flow and concentration fields, with the mixing angle varying between acute (q =10) and obtuse (q = 130) angles. Residence time dis- tributions are determined to study the effect of the angles on the mixing and velocity patterns, in particular, different flow regimes, i.e., stratified laminar, vor- tex, and engulfment flow. The results from the simulations are validated with liter- ature data and found to be in good agreement. Maximum mixing occurs in the 100 obtuse-angle Y-mixer, attributed to the extensive engulfment of flows in the mixing channel.<br
Keywords: Lattice Boltzmann methods; Micromixers; Computational fluid dynamics; Residence time distribution; Y-mixers